IMPACT OF DIVIDEND POLICY ON MARKET PRICE OF VIETNAMESE LISTED COMPANIES FROM 2010 TO 2017 - Hoàng Mai Phương; Nguyễn Thanh Hồng Ân (Tạp chí Khoa học Đại học Đà Lạt)
Using a sample of 133 listed firms on the Hochiminh Stock Exchange for the period from 2010 to 2017, this research finds evidence indicating that dividend policy does not affect a firm’s value. A robust test with a dynamic model using the System-GMM method confirms the results. The research results support the hypothesis that in less-developed financial markets, such as those in Vietnam, positive effects of paying dividends, as suggested by existing theories in finance, tend to be neutralized by the costs that firms have to endure due to insufficient cash. This might partially explain why dividend policy does not affect a firm’s value in Vietnam.